Information Retrieval System for Digital Libraries Using Fuzzy Logic - Ghaydaa Al-Talib; Nawar Ghani (Al-Rafidain Journal of Computer Sciences and Mathematics)
This research is one of the important steps towards processing the most significant challenge in digital libraries and web, which is computing document’s rank, its importance, and its relevance to the user information need. This is achieved through the utilization of fuzzy logic high potential capabilities in dealing with such sort of problems and providing notable flexibility for the user to get his favorite subjects. The research is concerned with designing and implementing a proposed information retrieval system, called FIRS (Fuzzy Information Retrieval System). This system is developed to deal with huge database, which contains different text file types and sizes. This database is distributed over a collection of server computers, connected with the intranet network that is dedicated for this system. The system has the ability for mining of data available in this database and retrieving the useful information that corresponds with the user need. This is accomplished through applying the proposed algorithms for indexing process, document’s rank computations, generating keywords process, and finally, displaying information retrieval results. The proposed system gives high quality results comparing with other information retrieving algorithms.